Effects of cosmetic and other camouflage interventions on appearance-related and psychological outcomes among adults with visible differences in appearance: a systematic review. Issue 3 (9th March 2021) - Gholizadeh, Shadi; Rice, Danielle B; Carboni-Jiménez, Andrea; Kwakkenbos, Linda; Boruff, Jill; Krishnan, Ankur; Malcarne, Vanessa L; Thombs, Brett D
Abstract : Objective: Visible differences in appearance are associated with poor social and psychological outcomes. Effectiveness of non-surgical cosmetic and other camouflage interventions is poorly understood. The objective was to evaluate effects of cosmetic and other camouflage interventions on appearance-related outcomes, general psychological outcomes and adverse effects for adults with visible appearance differences. Design: Systematic review. Data sources: MEDLINE (Ovid), EMBASE (Ovid), PsycINFO (Ovid) CINAHL and Cochrane Central databases searched from inception to 24 October 2020. Two reviewers independently reviewed titles and abstracts and full texts. Eligibility criteria: Randomised controlled trials in any language on non-surgical cosmetic or other camouflage interventions that reported appearance-related outcomes, general psychological outcomes or adverse effects for adults with visible appearance differences. Data extraction and synthesis: Two reviewers independently extracted data, assessed intervention reporting using the Template for Intervention Description and Replication checklist, and assessed risk of bias using the Cochrane risk of bias tool. Outcomes included appearance-related outcomes, general psychological outcomes (eg, depression, anxiety) and adverse effects. Results: One head-to-head trial and five trials with waiting list or routine care comparators were included. All had unclear or high risk of bias in at least five of seven domains. Effect sizes could not be determined for most outcomes due to poor reporting. Between-group statistically significant differences were not reported for any appearance-related outcomes and for only 5 of 25 (20%) other psychological outcomes. Given heterogeneity of populations and interventions, poor reporting and high risk of bias, quantitative synthesis was not possible. Conclusions: Conclusions about effectiveness of non-surgical cosmetic or other camouflage interventions could not be drawn. Well-designed and conducted trials are needed. Without such evidence, clinicians or other qualified individuals should engage with patients interested in cosmetic interventions in shared decision making, outlining potential benefits and harms, and the lack of evidence to inform decisions. PROSPERO registration number: CRD42018103421.